The theater of the absurd - Morales, Gabriela; Heras, Esteban
The Theater of the Absurd is a designation given to certain plays, written by some European playwrights that became famous in the 1940?s and 1950 s. This term, Theater of the Absurd, was coined by the Hungarian-born critic Martin Esslin in his 1962 book published with the same title. Esslin got the idea of absurd from the French philosopher Albert Camus, in his essay The Myth of Sisyphus. Even though this kind of theater arose after the Second World War, it has its origins in Ancient Greece, mainly with Aristophanes? theater. Later, we can find some absurdist elements in the Middle Ages. Also, German Expressionism contributed to the development of these elements. Finally, World War II was the event that brought the Theater of the Absurd to life. The plays of the Theater of the Absurd are characterized by nonsense dialogues, repetitive or meaningless action, and non-realistic or impossible plots. The most well-known play is Samuel Beckett?s Waiting for Godot. Boris Vian. They were all born in France. However, there were many other playwrights that were not born in France, but lived and wrote there, often in French. Some of these playwrights include Samuel Becket, from Ireland; Eugene Ionesco, from Romania, Arthur Adamov, from Russia, and Fernando Arrabal, from Spain. The Theater of the Absurd? has had a great influence on the whole world since its appearance, and it has become an inspiration for the modern Theater.